2021
DOI: 10.1021/acsaem.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Ultrareliable Composite Phase Change Material for Battery Thermal Management Derived from a Rationally Designed Phase Changeable and Hydrophobic Polymer Skeleton

Abstract: The development of phase change material (PCM) for battery thermal management poses key limitations on its reliability caused by leakage and shape deformation under high temperature. In this work, a kind of phase changeable and hydrophobic polymer skeleton is grown in situ in a paraffin (PA)/expanded graphite matrix to obtain the leakage-proof composite PCM (CPCM) at the kilogram-level. Benefiting from the additional latent heat provided by the phase changeable alkyl side chains of the polymer skeleton, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Paraffins, fatty acids, alcohols, esters and glycols are known organic PCMs. [7][8][9][10] However, their low thermal conductivity (0.1-0.35 W m À1 K À1 ) and flammability make them less effective and bring safety concerns. 11,12 Metallic PCMs are attractive because of their high thermal conductivity 13 and higher heat capacity than organic PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Paraffins, fatty acids, alcohols, esters and glycols are known organic PCMs. [7][8][9][10] However, their low thermal conductivity (0.1-0.35 W m À1 K À1 ) and flammability make them less effective and bring safety concerns. 11,12 Metallic PCMs are attractive because of their high thermal conductivity 13 and higher heat capacity than organic PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al 36 prepared the CPCM with EG and CF, which have an obvious synergistic enhancement action on the heat conduction capacity of PCM. Xiao et al 37 established a CPCM with a new thermosetting hydrophobic polymer (THP) skeleton, which could stably control the maximal temperature and maximal temperature difference at 50.9°C and 5.0°C, respectively, under 50 continuous cycles of 3 C and 4 C charge‐discharge. Li et al 38 prepared the CPCMs by adding grafted CNTs, and found that compared with adding ungrafted CNTs, it had better dispersion and heat conduction capacity.…”
Section: Introductionmentioning
confidence: 99%
“…During the long-term operation, the liquid-state PCM may gradually migrate onto the module surface, leading to the degradation of the thermal storage capacity of the CPCM module or even causing safety issues. For example, Xiao et al prepared a classical PA/EG/low-density polyethylene CPCM and observed a significant mass loss during 100 endothermic–exothermic cycles within the temperature range of 30–70 °C; Lin et al prepared a PA/EG/olefin block copolymer-based CPCM and found a leakage rate of more than 1 wt % in a vacuum drying oven at 60 °C. Furthermore, the rigid property of both the cells and the CPCM results in a rigid contact at the interface, which gives rise to a relatively high thermal contact resistance and compressive stress accumulation during complex driving conditions …”
Section: Introductionmentioning
confidence: 99%